Phoenix dactilyfera L. Pits Extract Restored Bone Homeostasis in Glucocorticoid-Induced Osteoporotic Animal Model through the Antioxidant Effect and Wnt5a Non-Canonical Signaling - Samar R. Saleh; Doaa A. Ghareeb; Aliaa A. Masoud; Eman Sheta; Mohamed Nabil; Inas M. Masoud; Adham M. Maher (MDPI AG, 2022)
Oxidative stress associated with long-term glucocorticoids administration is a route through which secondary osteoporosis can be developed. The therapeutic potential of Phoenix dactilyfera L. pits is offered by their balanced, valuable and diverse phytochemical composition providing protective potential against oxidative reactions, making it a good candidate to treat glucocorticoid-induced osteoporosis (GIO). This study evaluates the possible anti-osteoporotic effect of date pit extract (DPE) against dexamethasone (DEXA)-induced osteoporosis. Male rats were allocated into three control groups, which received saline, low and high doses of DPE (150 and 300 mg/kg/day), respectively. Osteoporosis-induced groups that received DEXA (1 mg/kg/day) were divided into DEXA only, DPE (2 doses) + DEXA, and ipriflavone + DEXA. Femoral bone minerals density and bone mineral content, bone oxidative stress markers, Wnt signaling, osteoblast and osteoclast differentiation markers, and femur histopathology were evaluated. DPE defeated the oxidative stress, resulting in ameliorative changes in Wnt signaling. DPE significantly reduced the adipogenicity and abolished the osteoclastogenic markers (RANKL/OPG ratio, ACP, TRAP) while enhancing the osteogenic differentiation markers (Runx2, Osx, COL1A1, OCN). In Conclusion DPE restored the balanced proliferation and differentiation of osteoclasts and osteoblasts precursors. DPE can be considered a promising remedy for GIO, especially at a low dose that had more potency.